Knowledge Sharing Digital Marketing Sebagai Upaya Membangun Jiwa Kewirausahaan Dari Produk Lokal Desa Sekarwangi - Khasanah, Fata Nidaul (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
The use of technology in the field of entrepreneurship has become a central point that plays a key role in shaping the contemporary business landscape. Rapid changes in technological developments have a significant impact on the way businesses operate, innovate and compete in the global market. In the current era, business actors are faced with the need to adapt to advances in digital technology in order to survive in business competition. Especially considering that most consumers make online purchase activities. Analysis of the condition of partner problems obtained that many local products have more selling value, such as palm sugar products, coffee products and lemongrass processed products. But the obstacle is related to product marketing. The village MSME players hope that their local products can be known to the wider community. Based on the phenomenon of problems faced by partners, knowledge sharing activities related to digital marketing are carried out as an effort to build an entrepreneurial spirit through three stages of activities, namely counseling, training, and mentoring. The results of the activity received a good response by partners, there was interest in partners to be able to market their local products digitally through the use of their mobile devices.